Interaction of STIL with FOXM1 regulates SF3A3 transcription in the hepatocellular carcinoma development - Haijun Zhang; Lin Zhang; Ziqi Wu (Cell Division)
Abstract Background Dysregulation of SF3A3 has been related to the development of many cancers. Here, we investigated the functional role of SF3A3 in hepatocellular carcinoma (HCC). Methods SF3A3 expression in HCC tissues and cell lines was examined using RT-qPCR. Changes in malignant behavior of HCC cells after downregulation of SF3A3 were assessed by EdU, colony formation, flow cytometry, wound healing, and Transwell invasion assays. Multiple datasets were combined to identify the upstream modifiers of SF3A3. The binding relationship between STIL and FOXM1 was explored by co-IP assay, and the effect of STIL and FOXM1 on the binding of FOXM1 at the SF3A3 promoter was detected by ChIP-qPCR assay. A xenograft tumor model was established to explore the changes of tumors in vivo, and the expression of Ki67, GPC3, and p53 in tumor tissues was detected by immunohistochemistry. Results SF3A3 and STIL were overexpressed in HCC tissues and cells, and downregulation of SF3A3 or STIL inhibited the malignant behavior of HCC cells by promoting the expression of p53. An interaction between STIL and FOXM1 regulated the SF3A3 expression in HCC cells. Knockdown of FOXM1 further enhanced the anti-tumor effects of STIL loss on HCC cells in vitro and in vivo, whereas SF3A3 overexpression overturned the impact of STIL loss on HCC cells in vitro and in vivo. Conclusions Our findings indicate that STIL/FOXM1 expedites HCC development by activating SF3A3, which highlights the importance of SF3A3 as a promising prognostic marker and therapeutic target for HCC.